Research about inclusive education: Are the scope, reach and limits empirical and methodological and/or conceptual and evaluative? - Norwich, Brahm (Frontiers in Education, 2022)
Abstract This paper argues for a broader conception about research into inclusive education, one that extends beyond a focus on empirical effects. It starts with a recent summary of international research into the effects of inclusive education on students with SEN / disabilities and those without. On the basis of this review, it examines a model showing the complexity of factors involved in asking questions about the effects of inclusive education. This complexity reflects the ambiguity and complexity of inclusive education, which is discussed in terms of varied contemporary positions about inclusive education. The analysis illustrates how there has been more focus on thin concepts of inclusion (as setting placement or in general terms) rather than its normative and value basis, which reflects a thick concept of inclusion. The paper concludes by illustrating with the use of a version of the capability approach how there are value tensions implicit in inclusion about difference and about personal versus public choice. This requires value clarification and some settlement about the balance of values, which is where deliberative democratic principles and processes have a crucial role. The proposed answer to the paper’s question about the scope, reach and limits of research in inclusive education is that such research involves both empirical, methodological and evaluative matters. Educational research about inclusive education is not just empirical, it also involves value and norm clarification, a process which has been too often ignored.